2014
DOI: 10.1093/jjco/hyu176
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing docetaxel-cisplatin combination with weekly docetaxel alone in elderly patients with advanced non-small-cell lung cancer: Japan Clinical Oncology Group (JCOG) 0207

Abstract: Objective: Prospective trials specifically designed for elderly patients with advanced non-small-cell lung cancer demonstrating the benefit of platinum-based therapies are still lacking. This trial was designed to clarify whether the addition of cisplatin to monotherapy could improve survival for elderly patients. Methods: Elderly patients (age ≥70 years, ECOG performance Status 0-1) with advanced non-smallcell lung cancer were randomized to receive docetaxel 20 mg/m 2 plus cisplatin 25 mg/m 2 on Day 1, 8and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…However, some studies report that the efficacy and toxicity of treatment with anticancer agents differ between the ages of 70 and 74 years and ≥75 years, and that elderly individuals should be defined as those aged ≥75 years [16,17]. In the present study, only 3 patients were aged ≤74 years, and 2 of them showed PD and received only one cycle of treatment.…”
Section: Discussionmentioning
confidence: 73%
“…However, some studies report that the efficacy and toxicity of treatment with anticancer agents differ between the ages of 70 and 74 years and ≥75 years, and that elderly individuals should be defined as those aged ≥75 years [16,17]. In the present study, only 3 patients were aged ≤74 years, and 2 of them showed PD and received only one cycle of treatment.…”
Section: Discussionmentioning
confidence: 73%
“…However, treatment-related death was 4.4% for patients with NSCLC >70 years of age undergoing carboplatinbased doublet chemotherapy and remained a serious problem. On the other hand, in Japan, although there was a phase III trial that was designed to clarify whether the addition of cisplatin to monotherapy could improve survival for elderly patients, this study showed cisplatin-based doublet chemotherapy could not significantly associate with survival benefits in patients with NSCLC ≥ 75 years of age [18]. Moreover, elderly patients have been defined as patients aged ≥ 75 years in ongoing clinical trials, including in the JCOG1210/ WJOG7813L study (UMIN000011460) of docetaxel versus carboplatin plus pemetrexed followed by pemetrexed as a first-line treatment in elderly patients with advanced non-squamous NSCLC in Japan.…”
Section: Discussionmentioning
confidence: 86%
“…ORR of the second-line chemotherapy was 9.2% [95% confidence interval (CI), [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in age ≥ 75 group and 12.2% (95% CI, 5-26) in age 70-74 group. There was no significance difference between the groups (p=0.75).…”
Section: Efficacymentioning
confidence: 99%
“…In those patients ≥75 years of age, toxicity was higher without any OS benefit. 167 Another Japanese study compared the same weekly schedule of cisplatin and docetaxel with docetaxel alone administered every 3 weeks in chemotherapy-naive patients ≥70 years and PS 0-1. This study failed to demonstrate any advantage of the combination over single agent.…”
Section: Systemic Treatment In the Elderlymentioning
confidence: 99%